Commercial aviation safety - Rodrigues, Clarence C.; Cusick, Stephen K.; Wells, Alexander T.; McGraw-Hill eBooks (New York, N.Y. : McGraw-Hill Education LLC., 2012)
"Presenting current practice and procedures from all major air traffic and regulatory agencies, this book covers the entire commercial aviation safety system--from human safety to accident investigation. Commercial aviation safety, fifth edition greatly expands the focus of the fourth edition to include the international and safety management systems (SMS) knowledge required by today?s aviation safety professional. Most aviation safety-related texts cover only issues related to the FAA and NTSB. However, as a practicing professional in the aviation field, one must also be knowledgeable about ICAO, SMS, OSHA, and EPA. This book delivers on this need. Offering a comprehensive analysis on the entire aviation safety system, this authoritative guide provides a broad understanding of aviation safety for students entering the field, and serves as a handy reference for the practicing aviation safety professional. Commercial aviation safety, fifth edition: now includes International Civil Aviation Organization (ICAO) regulations provides organization and rule-making process of all four relevant regulatory agencies in one place; contains expanded accident causation models Features new research on human factors in aviation safety offers new information on air traffic control and aircraft safety systems Includes updated airport and airline safety information; contains a new chapter on Safety Management Systems (SMS); provides knowledge on hot-button safety topics like runway incursions and security student learning features: chapter outlines with each major topic covered chapter objectives after the outline Heavily illustrated with tables, figures, and exhibits Key terms--each chapter ends with a listing of key terms used in the text review questions at the end of each chapter cover all the important points. A listing of suggested readings included after each chapter ".
8. Air traffic safety systems -- Learning objectives -- Introduction -- Basic components of the atc system -- Operational planning improvements -- The next generation air transportation system (nextgen) (www.faa.gov/) -- Key terms -- Review questions -- References -- 9. Aircraft safety systems -- Learning objectives -- Introduction -- Jet engine development -- Long-range commercial jet transport era -- Safety design for atmospheric conditions -- Flight deck human--machine interface -- Early cockpit development -- Flight procedures---takeoff, approach, and landing -- Modeling, design, and testing tools -- Future aircraft technologies -- Next generation flight operations -- Key terms -- Review questions -- References -- 10. Airport safety -- Learning objectives -- Introduction -- Airport certification -- Operational safety -- Runway incursions -- Conclusions -- Key terms -- Review questions -- References -- 11. Aviation security -- Learning objectives -- Introduction -- Review of attacks on civil aviation -- The regulatory movement -- Transportation security administration -- Role of intelligence -- Review of security technologies -- Conclusions -- Key terms -- Review questions -- References -- 12. Airline safety -- Learning objectives -- Introduction -- International development of airline sms -- The icao sms framework of safety components and program elements$1 (Bthe four pillars -- Development of airline sms in the united states -- Accident investigation and auditing -- Communications -- Training -- Role of alpa in airline safety -- Flight safety foundation -- Sms infrastructure at a major u.s. Airline -- Key terms -- Review questions -- References -- 13. Aviation safety management systems -- Learning objectives -- Introduction -- The evolution of sms principles -- The fundamental components of sms$1 (Bthe four pillars -- Safety risk management explained -- Safety assurance explained -- The future of sms in aviation -- Key terms -- Review questions -- References.s
Rev. ed. of: Commercial aviation safety / Alexander T. Wells. 2003.
Includes bibliographical references and indexes.
Also issued in online version.
Description based on cover image and table of contents, viewed on Apr. 22, 2015.
Keywords: Aeronautics -- United States -- Safety measures; Aeronautics, Commercial -- United States -- Safety measures; TRANSPORTATION / Aviation / General; Electronic books